Informație și fapt în comunicare - Lucian-Vasile SZABO (Eon, 2023)
Human communication means the transmission of informational content from one person to another. Information can be powerful, new, interesting, but we often encounter messages with quite limited informational content, with a limited area of interest, where often factual elements are combined with speculation or even fiction, lying also being a constant of communication. Everyone communicates, and specialists in the field are few. The result of message exchange depends on many factors, from data quality to the professionalism of the sender and the disposition of the end receiver. Under these circumstances, professional communication can be successfully achieved when specialists in the field manage to avoid pitfalls arising on the route of information exchange. It all starts with collecting the information that will be contained in the message, in the communication product. The operation shall be carried out according to clear rules, in order to avoid or reduce distortions. The purpose of this study is to present the prerequisites for the information gathering process.